2001
DOI: 10.1038/sj.ijo.0801639
|View full text |Cite
|
Sign up to set email alerts
|

Influence of orlistat on bone turnover and body composition

Abstract: OBJECTIVE:To investigate the in¯uence of the pancreas lipase inhibitor orlistat (OLS) on calcium metabolism, bone turnover, bone mass, bone density and body composition when given for obesity as adjuvant to an energy-and fat-restricted diet. DESIGN: Randomized controlled double-blinded trial of treatment with OLS 120 mg three times daily or placebo for 1 y. SUBJECTS: Thirty obese subjects with a mean body mass index (BMI) of 36.9 AE 3.7 kgam 2 and a mean age of 41 AE 11 y. Sixteen patients were assigned to OLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 40 publications
(30 reference statements)
1
27
0
1
Order By: Relevance
“…The changes in lumbar spine and total body BMD from pre-treatment to 12 months were not significant in either group. Significant weight losses of 11.2 ± 7.5 kg (mean ± SD) and 8.1 ± 7.5 kg were measured in the orlistat and placebo groups, respectively, albeit the difference between groups was not significant in this particular trial [79].…”
Section: Orlistatmentioning
confidence: 62%
See 1 more Smart Citation
“…The changes in lumbar spine and total body BMD from pre-treatment to 12 months were not significant in either group. Significant weight losses of 11.2 ± 7.5 kg (mean ± SD) and 8.1 ± 7.5 kg were measured in the orlistat and placebo groups, respectively, albeit the difference between groups was not significant in this particular trial [79].…”
Section: Orlistatmentioning
confidence: 62%
“…A single clinical trial suggests that orlistat is not associated with any loss of BMD or bone mineral content (BMC) over and above the effect of placebo and associated weight loss [79]. This 12-month, prospective, randomized, placebo-controlled trial of orlistat treatment (120 mg, 3 times a day) in 30 obese participants with a mean age of 41 ± 11 years, showed that mean forearm BMD decreased significantly by 0.01 g/cm 2 from pre-treatment values to 12 months in the orlistat group, with no difference in treatment effect between the orlistat and placebo groups.…”
Section: Orlistatmentioning
confidence: 99%
“…8,59 Only one study of 16 subjects treated with orlistat met the inclusion criteria. 25 The effects of sibutramine on FFM loss are also understudied, with only two studies including only 27 subjects meeting the inclusion criteria. 34,33 It is of note that the %FFML in both these small studies was higher than could be expected for the associated LCD, raising significant concern about the components of weight loss with this medication.…”
Section: Discussionmentioning
confidence: 99%
“…In this placebo controlled RCT, orlistat caused a marginal increase in weight loss, but made no change to the proportion of weight loss consisting of FFM compared to a LCD alone (Table 2). 25 Surgically induced weight loss When compared to LAGB, both BPD (Po0.001) and RYGB (P ¼ 0.002) caused greater %FFML. The median (IQR) %FFML was 25.6 (11), 31.3 (12.2) and 17.5 (3.7)% following BPD, RYGB and LAGB, respectively.…”
Section: Pharmaceuticals Studiesmentioning
confidence: 91%
“…A 12-month study of orlistat treatment in adolescents resulted in a decrease in BMi by 0.55 kg/m 2 in the treated group versus BMi gain of 0.31 in the controls (Chanoine et al, 2005). Orlistat therapy may reduce fat soluble vitamin levels (A, D, E, K) due to lipase inhibition and has frequently reported unpleasant side effects including flatus (Gotfredsen et al, 2001). Monitoring of 25-OH vitamin D levels during therapy and supplementation of fat soluble vitamins is recommended.…”
Section: Medicationsmentioning
confidence: 99%